Social Science Learning through Cooperative Script Aplication: Development Strategy of Coorperative and Opinion Appreciation Character for Elementary School Students - suwarti suwarti; Mohammad Zainuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2017)
Many elementary school students today bring its own problems with the dissolution of cooperative and opinion appreciation character. Especially at this era of implementation character based 2013 curriculum. Therefore, it is necessary to find a solution to overcome it. After going through a series of studies, then selected solution in the form of development strategy of coorperative and opinion appreciation character for elementary school students. This research has done in the research development approach. So it will produce the product of learning video as reference material for teacher. In this research the researcher appoints students of elementary school program as model teacher. The results showed that the implementation of social science learning application of coperative script strategy, all strategy steps have been done and have an impact on the development of the character of cooperation and opinion apprecdiation of the students especialy in social science learning. Thus it can be concluded that the development of social science through cooperative script strategy effective and efficient to reestablish the character of cooperation and opinion appreciation on self elementary students.